The Role of Islamic Religious Education Teachers in Fostering Student Morals at MTS Al-Hikmah Cupel (Jurnal Al-Fikrah, 2023)
Moral degradation in the development of early childhood towards old age, especially for the children of Madasah Tsanawiyah, is a very interesting topic for study. The reason is, many of them only rely on formal education but forget about moral education and self-behavior in order to improve morality as an educated person. This attitude then became an attraction for the author to conduct research on the role of Islamic Religious Education teachers in fostering student morals. The formulation of the problem in this study is how the role of Islamic Religious Education teachers in fostering morality towards students at MTs al-Hikmah cupel. The purpose of this study was to find out how the role of Islamic Religious Education teachers plays in fostering morality towards students at MTs al-Hikmah Cupel. In this case, students of MTs al-Hikmah Cupel. The research that will be carried out is using a descriptive qualitative approach, because the research to be carried out is trying to obtain a description and description of the role of Islamic education teachers at MTs al-Hikmah Cupel with data collection techniques using structured interviews, direct observation and documentation. This study describes some of the roles of PAI teachers on student morality at MTs al-Hikmah Cupel, namely: First; The role of teaching in educating students with high quality knowledge, second; The role of education in fostering the character and behavior of students who are elegant and, third; The role leads to religious education in order to be able to carry out good and right worship.